The Influence of Restrictive Pulmonary Dysfunction on Osteoporotic Thoracic Vertebral Fractures - Ji-Hun Park; Sang-Min Lee; Seong-Woo Shim; Sung-Nyun Baek; Yong-Soo Choi (Asian Spine Journal, 2021)
Study Design A cross-sectional study. Purpose To examine the influence of restrictive pulmonary dysfunction on osteoporotic thoracic vertebral fractures. Overview of Literature Osteoporotic thoracic vertebral fractures generally result in an increased kyphotic angle, which in turn may lead to pulmonary function impairment. Impaired pulmonary function could be associated with vertebral fractures. However, an association between osteoporotic thoracic vertebral fractures and pulmonary function remains controversial. Methods A total of 96 patients were enrolled in this study, 30 of whom had osteoporotic thoracic vertebral fractures (group 1), 30 with chronic back pain (group 2), and 36 with chronic pulmonary diseases (group 3). Radiologic study of prevalent vertebral fractures, thoracic kyphotic angle, bone mineral density, relaxed expiratory vital capacity, forced vital capacity (FVC), and forced expiratory volume in 1 second (FEV1) in spirometry was investigated. Results The mean FVC and FEV1 were 75.66%±20.23% and 79.93%±22.48%, respectively, in group 1; 84.50%±16.25% and 91.87%±21.65%, respectively, in group 2; and 91.64%±17.53% and 91.03%±23.71%, respectively, in group 3. Group 1 (patients with osteoporotic thoracic vertebral fracture) had the lowest FVC among the three groups (p=0.01). Group 1 revealed worse result of pulmonary dysfunction than group 3 (patients with chronic pulmonary diseases) (p=0.01). The average kyphosis angle of the thoracic spine was 26.95°±15.17°, 36.47°±20.08°, and 28.58°±10.58° in groups 1, 2, and 3, respectively. There was a negative correlation between thoracic kyphosis and FEV1 (r=−0.309, p=0.01). Conclusions The results suggest that osteoporotic thoracic vertebral fracture burden could be affected by restrictive pulmonary dysfunction.